Effect of electrolyte age and potential changes on the morphology of TiO2 nanotubes - Sopha, Hanna; Hromádko, Luděk; Nechvílová, Kateřina; Macák, Jan M. (Elsevier, 2015)
In the present work we report on the influence of the age of ethylene glycol-based electrolytes on the synthesis of self-organized TiO2 nanotube layers. Electrolytes of different ages, defined by the total duration for anodization, were explored in order to get an insight into how the tube structure changes with the electrolyte age. The results show a strong dependence of the electrolyte age upon the nanotube length and diameter — a phenomenon surprisingly not discussed in existing literature. When fresh electrolytes are employed, nanotube arrays with a high aspect ratio are received, while in older electrolytes (i.e. already used for anodization) the nanotube arrays exhibit low aspect ratios. This is a very important aspect for the reproducible synthesis of the nanotube layers. Moreover, the effect of the potential on the nanotube dimensions was investigated. Linear dependence of the diameter upon the potential was observed. Last, but not least, the influence of a potential change towards the end of the anodization time was studied. By sweeping the potential to 100 V, or to 5 V and keeping this for 1 h after applying a constant potential of 60 V for 4 h, nanotubes underwent interesting morphological changes. In particular, when slow sweeping from 60 V to 5 V was carried out, small nanotubes grew in the gaps between the initial nanotubes. Interestingly, these nanotube layers showed lower adhesion to the underlying substrates.
Keywords: Anodization; Adhesion; Electrolyte age; Nanotubes; Titanium dioxide